SKIP Downregulation Increases TGF-β1-Induced Matrix Metalloproteinase-9 Production in Transformed Keratinocytes - Jelena Kocić; Victor Villar; Aleksandra Krstić; Juan F. Santibanez (Scientifica)
Transforming growth factor-beta (TGF-β1) is a potent inductor of matrix metalloproteinase-9 (MMP-9) in transformed cells. Recently, Ski-interacting protein (SKIP) has been described as a regulator of TGF-β1 signal transduction, but its role in the induction of cell malignance by TGF-β1 has not been fully elucidated so far. In the present study, we analyzed the role of SKIP on TGF-β1-induced MMP-9 production. Mouse transformed keratinocytes (PDV) were stably transfected with SKIP antisense construct. We observed that SKIP depletion provoked an enhancement in the expression of MMP-9 in response to TGF-β1 treatment. The downregulation of SKIP produced an enhancement in TGF-β1-activated ERK1,2 MAP kinase as well as increased transactivation of downstream Elk1 transcription factor. The increased MMP-9 production in response to TGF-β1 was dependent of MAPK activation as PD98059, an MEK inhibitor, reduced MMP-9 expression in SKIP antisense transfected cells. Thus, we propose SKIP as a regulatory protein in TGF-β1-induced MMP-9 expression acting by controlling ERK1,2 signaling in transformed cells.